Like Frying Multiple Eggs in One Pan: a Qualitative Study Exploring the Understanding of Inter-speciality Training in Cancer Care - McInally, W; Benstead, K; Brandl, A; Dodlek, Nikolina; De Munter, J.; Gasparotto, C; Grau-Eriksen, J; Kelly, R G; Lecoq, C; O'Higgins, N; Schlüter, Oliver K.; Popović, Maša; et al. (My University, 2023)
H igh-quality cancer care is a key priority worldwide. Caring for people affected by cancer requires a range of specific knowledge, skills and experience to deliver the complex care regimens both within the hospital and within the community environment. In June 2022, the European Cancer Organisation along with 33 European cancer societies began working together to develop a curriculum for inter-speciality training for healthcare professionals across Europe. As part of the project, this research consisted of a qualitative survey distributed to the European Union societies via email. The aim of this paper is to disseminate the qualitative findings from healthcare professionals across Europe. Questionnaires were sent out to a convenience sample of 219 healthcare professionals and patient advocates with a response rate of 55% (n = 115). The findings identified that there were four key themes: 'What is inter-speciality training?', 'Barriers and challenges', 'Support throughout the cancer journey' and 'New ways of working'. These results are part of a larger needs analysis and scoping review to inform the development of a core competency framework which will be part of an inter-speciality curriculum for specialist cancer doctors, nurses and other healthcare professionals across Europe. Healthcare professionals will be able to access education and training through the virtual learning environment and workshops and by clinical rotations to other specialties.
Keywords: Cancer; Care; Education; Experiences; Healthcare professionals; Inter-specialty training